«MAN» - «АДАМ» КОНЦЕПТОСФЕРАСИ БИРЛИКЛАРИНИНГ ЛИНГВОМАДАНИЙ ХУСУСИЯТЛАРИ - Кдырбаева, Г.К.; Султанова, М. (SCIENCE and SOCIETY, 2018)
The article deals with the analysis of the concept "Man-адам" in the Karakalpak national view of the world. The investigation was done on the basis of the conceptual analysis. A lexis unit "man-адам" was analyzed with the help of the etymological dictionary of the Turkic languages and monolingual English dictionary, which will serve as a preparatory stage for further investigations in conceptual analysis.